Etika Bermedia Sosial dalam Upaya Pemahaman Literasi Digital di SMPN 4 Pasir Putih - Innosensia E.I. Ndiki Satu; Angela A. Baptista; Fransiska N. Ola; Ermelinda S. Ndarung (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The use of social media is very beneficial in human life. The use of social media has many positive and negative impacts. If not used properly, the use of social media will have negative consequences. One of the impacts of social media use is a lack of understanding regarding privacy issues. The purpose of this activity is to provide an understanding of the positive and negative impacts of social media use. This activity was carried out at SMPN 4 Pasir Putih, Nagawutung District, Lembata Regency. The results of the activity implementation show that the students of SMPN 4 Pasir Putih are very interested in participating in this socialization activity. They also better understand the positive and negative impacts of social media use.